The impact of Covid-19 on sport - Grix, J.; Brannagan, P. M.; Grimes, H.; Neville, R. (International Journal of Sport Policy and Politics, 2020)
The Covid-19 pandemic has had an unprecedented impact on society, leading to a rapid closure of businesses, places of work, worship, social engagement, schools and universities. Sport is often seen - along with the arts - as a trivial pursuit, categorised under `hobbies` or things to do once the serious business is over. However, this critical commentary argues that sport and sports events play a crucial social role even under normal circumstances. To this end we analyse the impact of Covid-19 on three areas of sport: first, the nature of elite sport played `without spectators` is discussed and what this means for the necessary `feelgood` factor associated with watching and following it; second, we look at Covid`s impact on the provision of sport for those in less well-off areas, drawing on a case study of Oldham during the pandemic. Finally, we analyse the severe economic and social impact of the pandemic on grassroots sports, including the relationship between mass and elite sport. This commentary seeks to stimulate wider interest on how Covid-19 has changed sport at elite and grassroots level and how the pandemic has led to differential outcomes for people from a variety of socio-economic backgrounds. Based on the above, the commentary assesses the likely long-term consequences of the Coronavirus pandemic on sport.